Luteolysis and pregnancy outcomes in dairy cows after treatment with estrumate or lutalyse - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2009)
In Experiment 1, lactating dairy cows (n = 1,230) in 6 herds were treated with 2 injections of prostaglandin F2α(PGF2α) 14 days apart (Presynch), with the second injection administered 12 to 14 days before the onset of a timed AI protocol (Ovsynch). Cows were inseminated when detected in estrus after the Presynch PGF2αinjections. Cows not inseminated were enrolled in the Ovsynch protocol and were assigned randomly to be treated with either Estrumate or Lutalyse as part of a timed artificial insemination (AI) protocol. Blood samples were collected before treatment injection (0 hour) and 48 and 72 hours later. In cows having progesterone concentrations ≥1 ng/mL at 0 hour and potentially having a functional corpus luteum (CL) responsive to a luteolytic agent, Lutalyse increased (P<0.05) luteal regression from 83.9 to 89.3%. Despite a significant increase in luteolysis, pregnancy rate per AI did not differ between treatments. Fertility was improved in both treatments in cows having reduced progesterone concentrations at 72 hours and in those showing signs of estrus. In Experiment 2, an ovulation resynchronization (Ovsynch-Resynch) program was initiated with gonadotropin-releasing hormone (GnRH) or saline in 427 previously inseminated lactating dairy cows of unknown pregnancy status in 1 herd. Seven days later, pregnancy was diagnosed and nonpregnant cows were blocked by number of CL and assigned randomly to receive Estrumate or Lutalyse. Diameter of each CL was recorded and blood samples were collected at 0 and 72 hours after treatment to assess serum progesterone. A fixed-time AI was given at 72 hours after treatment and approximately 16 hours after a GnRH injection to induce ovulation. Lutalyse increased(P<0.05) luteal regression from 69.1 to 78.5% regardless of the number of CL present or the total luteal volume per cow exposed to treatment. Pregnancy rate per AI did not differ between treatments. Although Lutalyse was slightly more effective than Estrumate in inducing luteolysis in lactating dairy cows exposed to an Ovsynch or Ovsynch-Resynch protocol, resulting pregnancy outcomes did not differ between products.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Reproduction; Estrus; Fertility; Luteolysis; Ovulation; Timed artificial insemination